Pendekatan medium hibrid dalam karya - Elun, Loros. (University Malaysia Sarawak, UNIMAS., 2006)
Changes in new era has witnessed the flows of arts and development of material usage. In our country, the used of medium based on hybridization had shown its maturity in contemporary arts era. This leads to development of hybrid medium usage in designing sorts of artworks such as a sculpture. This hybridization process is a combination of some different material substances that emphasize that emphasize the concept of contemporary art.